Tajdīd Ta’līm Mahārah al-Qirāah (Taḥlīl Ḍarūrah Adawāt al-Istifhām fi Ta’līm Mahārah al-Qirāah) - Rusdi Rusdi (ALSINATUNA, 2017)
Reading is one of the four language skills that have an important role in daily life. The way andcharacteristics of asking questions (istifham) are influential in achieving the objective of reading comprehension of a text. The use of questions (istifham) also stimulates students to understand reading texts and foster their critical thinking. All Arabic teachers, especially those who teach reading skill, should understand and master a questioning strategy to ease comprehending the text. Hopefully, this study can be used as a confirmation of theory in the fact that there is a parallel line between the theory of istifham in the teaching of reading  skill, and the process of understanding the passage.